Novel tooling for direct melt impregnation of textile with variotherm injection moulding: Methodology and proof of concept. (December 2022) - Werlen, Vincent; Rytka, Christian; Wegmann, Stephanie; Philipp, Halime; Khalaf, Yara; Michaud, Véronique; Brauner, Christian; Dransfeld, Clemens
Thermoplastic compression resin transfer moulding coupled with injection moulding is an appealing process for the production of thermoplastic composites. However, its implementation at an industrial scale remains challenging as variotherm injection moulding could prevent solid skin formation in the parting line, making cavity sealing difficult. In this study, a tool for thermoplastic compression resin transfer moulding and the related methods and process parameters for an implementation at an industrial scale are presented. The validity of the concept is proved by producing and characterizing composite plates with elevated fibre volume fractions and advantageous mechanical properties at a range of production temperatures within a cycle time not exceeding 20 min. The best mechanical properties were obtained at a production temperature of 270°C with a bending strength of 477 MPa, a flexural modulus measured at 25.7 GPa and a fibre volume content of 67%.